Beyond the text: a contrastive analysis of two Chinese translations of Gone with the Wind, undertaken from the perspective of Polysystem theory - Feng, Ziyi (Nanyang Technological University, 2023)
Traditional translation studies focus mainly on translated works, assessing various translations and evaluating their merits and demerits. Polysystem theory introduces a historical perspective and emphasizes the analysis of the translation process. It arguably provides a new perspective for translation studies.